2017
DOI: 10.1016/j.jtcvs.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Active clearance chest tubes: Awaiting randomized data

Abstract: Anaheim, Calif) is a commercially available chest tube that contains a guidewire-based clearance mechanism to maintain chest tube patency. To date, retrospective studies have shown that ATC chest tubes may reduce bleeding complications after heart surgery in certain patient populations. 1-3 A secondary benefit uncovered in previous study was a reduced rate of postoperative atrial fibrillation (POAF) with use of ATC chest tubes, thought to be related to reduced atrial irritation from improved mediastinal draina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[ 85 ] who found a link between new onset atrial fibrillation and pleural effusion. Similarly, Anderson [ 86 ] also showed that self-clearing chest tubes may reduce POAF although a randomized data is still needed to prove this claim. Interestingly a systematic review by Gozdek et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 85 ] who found a link between new onset atrial fibrillation and pleural effusion. Similarly, Anderson [ 86 ] also showed that self-clearing chest tubes may reduce POAF although a randomized data is still needed to prove this claim. Interestingly a systematic review by Gozdek et al .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the finding by Brookes et al [85] who found a link between new onset atrial fibrillation and pleural effusion. Similarly, Anderson [86] also showed that selfclearing chest tubes may reduce POAF although a randomized data is still needed to prove this claim. Interestingly a systematic review by Gozdek et al [87] showed that posterior pericardial drainage to minimize any possibility of pericardial tamponade could reduce the odds of POAF by 58% indicating that POAF is possibly associated with pericar-dial collections.…”
Section: Post-operative Outcomesmentioning
confidence: 97%